Complex impedance and electrical conduction analysis of Ho2O3 doped CaCu3Ti4O12 NTC ceramics - Guang-Tan Miao; Zhen-Jie Wang; Peng Li; Ji-Gong Hao; Wei Li; Juan Du; Wei-Fang Han; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Journal of Asian Ceramic Societies, 2022)
The structure and electrical properties of CaCu3Ti4O12 (CCTO) ceramics doped with xHo2O3 synthesized by solid-phase reaction method were systematically studied. Insights from X-ray diffraction (XRD) measurements indicate the existence of a primary phase of CCTO in all samples. Ho2O3 dopant was found to inhibit grain growth and thus leading to a reduced grain size of ceramics. Moreover, the distribution of resistivity with temperature revealed the manifestation of a negative temperature coefficient (NTC) effect in the samples. More specifically, the resistivity (ρ20) values of obtained ceramics configurations decreased from 8.54 × 106 to 1.76 × 105 Ω cm with increasing Ho2O3 doping content. In addition, thermal constant (B20/75) of all samples was higher than 4000 K. Electrical properties analysis disclosed that electron hopping process is main conduction mechanism within CCTO-based ceramics. In addition, insights from complex impedance spectra revealed the existence of grain boundaries with resistance higher than grains resistance. This effect is strongly connected with the manifestation of electrical relaxation procedures within grain boundaries. Our outcomes verify that both the structural configuration and the electrical performance of the CCTO-based ceramics can be tuned directly and effectively by incorporating Ho2O3 dopant.